Um estudo sobre a utilização das práticas contábeis e financeiras no processo decisório das empresas tecnológicas do arranjo produtivo local de Santa Rita do Sapucaí MG O Vale da Eletrônica - Paiva, Benedito Geovani Martins de (2012)
The Local Productive Arrangement (APL) of Santa Rita do Sapucaí in Minas Gerais state, called "The Electronics Valley" is comprised of technology-based companies, which receive influence of the entrepreneurial environment formed by the integration between them and the government and educational structure. The main objective of this study is to investigate whether these companies use the information provided by accounting and apply the techniques of financial management in decision making. In this scenario, defined as a matter of problem: Are the firms of the "Valley of Electronics" using the financial and accounting practices in the decision-making process? The motivation for this research was the assumption that the vast majority of companies in the "Valley of Electronics" does not use the full potential of accounting and financial management tools to assist decision making. Based on this hypothesis, in order to achieve the objective mentioned above, the research focused thirty-seven small, medium and large electronics firms in Santa Rita do Sapucaí. The results of such research reveal that the small and medium businesses use the accounts only as an instrument to meet the taxman. The bookkeeping largely offices is performed by third parties (78.38%) and the priority is information tax and labor. To control and decision making, it was evident that the prevailing financial management tools, developed largely in parallel to the accounts. The tools most commonly used are receivable and payable accounts, inventory control and cash flow. These controls allow the surveyed firms remain on the market, even without the use of traditional financial statements